Dynamic structural changes of supported Pd, PdSn, and PdIn nanoparticles during continuous flow high pressure direct H2O2 synthesis - Doronkin, Dmitry; Wang, Sheng; Sharapa, Dmitry I.; Deschner, Benedikt J.; Sheppard, Thomas L.; Zimina, Anna; Studt, Felix; Dittmeyer, Roland; Behrens, Silke; Grunwaldt, Jan-Dierk (Catalysis science & technology, 2020)
The direct synthesis of hydrogen peroxide over TiO2-supported mono- and bimetallic Pd, PdSn, and PdIn nanoparticles (NPs) was performed in a continuous plug-flow reactor at 80 bar in ethanol with H2 : O2 ratios varied from 10 : 1 to 1 : 10. At the same time the catalysts were monitored by operando X-ray absorption spectroscopy (XAS). The setup optimized for XAS allowed productivities that are among the highest reported up to now. A rate of up to 580 mmolH2O2 gcat−1 h−1 and a H2O2 concentration of 80 mmol l−1 were obtained which were only limited by the supply of reactants. During H2O2 synthesis, the studied NPs revealed a face centered cubic (fcc) Pd(Sn/In) metal (alloy) structure at H2 : O2 ratios equal to or smaller than 1 and the corresponding β-hydride structure at H2 : O2 > 1. Under all conditions, additional SnO2/In2O3 species were observed for the bimetallic catalysts. XAS supported by DFT calculations showed that alloying Pd with In or Sn limited the H2 uptake capacity and the corresponding lattice expansion of the bimetallic NPs. Different catalysts performed best at different H2 : O2 ratios. All catalysts were stable at H2 : O2 > 1. Significant leaching of the active Pd and PdIn species could be observed for H2 : O2 ≤ 1 (quantified by XAS), while PdSn was relatively stable under these conditions. The higher stability of PdSn NPs is proposed to be due to a SnO2 shell providing strong bonding between the NPs and the titania support.